Playful cultures and literacy: Considerations on teaching and learning in the context of the COVID-19 pandemic - Azevedo, Nair Correia Salgado de; Vieira, Julyara Grace; Oliveira, Sabrina Maria de Souza (Seven Editora, 2023)
The general objective of this work was to understand how the work with playful cultures occurred in the context of literacy (1st year of elementary school) through remote teaching. As specific objectives, this study intended: a) To discuss the concept of playful cultures relating them to the processes of literacy and literacy; b) Understand the literacy process of the child in the 1st year of elementary school; c) Demonstrate the vision of teachers on the possibility of working with the playful in the context of literacy and their strategies through remote teaching. This research is characterized as qualitative, bibliographical, documentary and exploratory. Several techniques were used for data collection, such as research in publications of the Capes database, virtual libraries and websites of scientific journals between the years 2010 and 2021 on the subject; documentary analysis of the process of legalization and standardization of remote learning during the pandemic; the application of a questionnaire to generate data on teachers' views on playfulness and literacy during the Covid-19 pandemic. We conclude that the playful cultures were witnessed in this context through virtual games adapted from face-to-face to remote teaching. Despite the obstacles, we realized that the valorization or not of the playful cultures does not depend only on the teachers, but on other factors besides the planning, such as the lack of access that, in addition to compromising the interaction of the students, also affected the process of literacy and literacy. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-045